Fiat: a good product with a wrong strategy. Issue 1 (19th April 2013) - Mullick, N.H.; Tripathi, Gaurav
Abstract : Subject area: Marketing, distribution channels and servicing, product portfolios. Study level/applicability: This case is suitable for students of business schools specialising in marketing. It is appropriate for students of marketing management and marketing strategy, distribution management and other related subjects. Case overview: The case focuses on the debacle of Fiat in India after its recent joint venture pertaining to dealership and servicing ended. The future is unclear and is the topic for debate. Expected learning outcomes: The case will help students to understand the reasons for the failure of Fiat in India and to be able to connect the case with the marketing concepts, especially those pertaining to distribution channels. Supplementary materials: Teaching notes are available for educators only. Please contact your library to gain login details or emailsupport@emeraldinsight.com to request teaching notes.